The Effect of Electronic Word of Mouth (ewom) and Halal Label on Purchase Decisions for Mixue Products - Anisa Sekar Ningrum; Btari Mariska Purwaamijaya; Adi Prehanto (Universitas Pendidikan Indonesia (UPI), 2023)
Currently, various types of food are widely circulated in the market, making consumers must be selective in choosing food. One of the trends is the Mixue ice cream brand. Mixue is a franchise brand from China that the public favors because of its affordable prices and many menu variants. Mixue is utilizing social media as a promotional medium. News about the halal status of Mixue which is a trend of conversation in the community on social media can result in a decrease in consumer purchase decisions, this is one of the impacts of electronic word of mouth (ewom). This study aims to analyze the effect of ewom and halal labels on purchase decisions for Mixue products. This research uses quantitative methods with an associative approach. The number of samples in this study were 60 respondents with a non-probability sampling technique of purposive sampling type. The results of the study stated: 1) ewom has a positive and significant effect on purchase decisions. 2) halal labeling has a positive and insignificant effect on purchase decisions. 3) ewom and halal label simultaneously positively and significantly affect purchase decisions. The implication of this research is that ewom can be used as a marketing medium and make it easier for consumers to search for product information, and the halal label will add value to a product that can increase consumer confidence to buy and consume products.